PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DALAM MEMBENTUK LOYALITAS PELANGGAN PADA PT. KARYA SUKA ABADI (GOODYEAR) PEKANBARU - Novella Indriani; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to determine the effect of product quality and service quality on customers in shaping customer loyalty. The type of research used is explanatory research with a quantitative approach. The sample is 91 respondents who are customers of PT. Karya Suka Abadi (Goodyear) Pekanbaru, using a questionnaire with a likert scale meansurement. The results showed that product quality had a direct and significan effect on customer satisfaction. The service quality variable has a direct on customer satisfaction. The customer satisfaction variable has a direct and significant effect on customer loyalty. Product quality variable has a direct and significant effect on customer loyalty. The service quality variable has a direct and significant effect on customer loyalty. Thus, it is better if PT. Karya Suka Abadi (Goodyear) Pekanbaru continues to maintain product quality and service quality so that comsumers feel satisfied and loyal to PT. Karya Suka Abadi (Goodyear) Pekanbaru. Key Words: Product Quality, Service Quality, Customers Satisfaction, Customers Loyalty